PENGARUH STRATEGI PEMASARAN TERHADAP KINERJA PEMASARAN PRODUK OLAHAN KOPI - Shalsabillah Nur Fitria; Sri Widayanti; Dona Wahyuning Laily (University of Jember, 2022)
Fore Coffee is a contemporary coffee shop offering a wide variety of high-quality coffee drinks. As coffee shops in Indonesia mushroomed during the COVID-19 pandemic, Fore Coffee carried out various marketing strategies so that sales could survive in an increasingly competitive market. This research aims to describe the 7P marketing components that Fore Coffee has carried out, analyze the effect of the 7P marketing strategy that Fore Coffee has carried out on marketing performance, and explain the implications of the research results for company development. The method in this study uses descriptive analysis and a PLS analysis tool named WarpPLS 6.0 with 100 respondents who are Fore Coffee consumers at Tunjungan Plaza Mall Surabaya. The results showed that the components of the 7P strategy carried out by Fore Coffee were considered quite good by most consumers. In testing the marketing strategy on the marketing performance of Fore Coffee, it was found that all components of the marketing strategy in this study had a significant effect on the acceptance of all research hypotheses. Based on the implications of the research results, theoretically justify and strengthen several theories and previous research.